Bidirectional Mendelian randomization study of insulin-related traits and risk of ovarian cancer - Wang, Xinghao; Sun, Jing; Li, Jia; Cai, Linkun; Chen, Qian; Wang, Yiling; Yang, Zhenghan; Liu, Wenjuan; Lv, Han; Wang, Zhenchang (Frontiers in Endocrinology, 2023)
Background It is well known that the occurrence and development of ovarian cancer are closely related to the patient’s weight and various endocrine factors in the body. Aim Mendelian randomization (MR) was used to analyze the bidirectional relationship between insulin related characteristics and ovarian cancer. Methods The data on insulin related characteristics are from up to 5567 diabetes free patients from 10 studies, mainly including fasting insulin level, insulin secretion rate, peak insulin response, etc. For ovarian cancer, UK Biobank data just updated in 2021 was selected, of which the relevant gene data was from 199741 Europeans. Mendelian randomization method was selected, with inverse variance weighting (IVW) as the main estimation, while MR Pleiotropy, MR Egger, weighted median and other methods were used to detect the heterogeneity of data and whether there was multi validity affecting conclusions. Results Among all insulin related indicators (fasting insulin level, insulin secretion rate, peak insulin response), the insulin secretion rate was selected to have a causal relationship with the occurrence of ovarian cancer (IVW, P < 0.05), that is, the risk of ovarian cancer increased with the decrease of insulin secretion rate. At the same time, we tested the heterogeneity and polymorphism of this indicator, and the results were non-existent, which ensured the accuracy of the analysis results. Reverse causal analysis showed that there was no causal effect between the two (P>0.05). Conclusion The impairment of the insulin secretion rate has a causal effect on the risk of ovarian cancer, which was confirmed by Mendel randomization. This suggests that the human glucose metabolism cycle represented by insulin secretion plays an important role in the pathogenesis of ovarian cancer, which provides a new idea for preventing the release of ovarian cancer.